(untitled) (Global Journal of Management and Business Research, 2014)
Following the globalization of financial markets, Taiwan opened up for security lending in July 2007 to attract Qualified Foreign Institutional Investors (QFIIs) to participate in Taiwan’s equity markets. Based on the security lending data, this paper uses systematic trading and generalized autoregressive conditional heteroscedasticity model (EGARCH) to investigate the volatility of returns in Taiwan futures market. The evidence suggests that during the financial crisis, the leverage effect has declined due to the involvement of QFIIs in security lending. The Taiwan futures market has become more stabilized. Secondly, including the security lending data, we find that the leverage effect is the Granger cause of short selling by QFIIs. Finally, the Multi Charts program trading experimental results show that QFIIs are informed traders and the investment performance can be improved with the information of security lending.